Fundamentals of acoustic signal processing - Toyama, M. (Mikio)
Fundamentals of Acoustic Signal Processing serves as an introduction to the previously published book The Nature and Technology of Acoustic Space. As a comprehensive, introductory text to modern acousticsand signal processing, it will be invaluable to students, researchers, and practitioners in industry. The book provides the fundamentals of acoustic wave theories as well as discrete signal processing. The authors have concentrated on the fundamental issues which they use in lecture courses, seminars, research, and development activities. From wave equations to discrete signal analysis, the treatment is self-contained with numerous helpful illustrations and examples. The relationship between continuous and discrete sampled data is clearly interpreted, and the origin of the sample data is readily comprehensible. Both students and engineers can reorganize their fundamental knowledge about signal processing. . Emphasis on the relationship between continuous and discrete signal representations. . Coverage of prevailing trends . High calibre data and figures. As a comprehensive, introductory textbook to modern acoustics and signal processing, this book will be essential to students, researchers and practitioners in industry.